Linguistic explication of rational and irrational knowledge types in the content of toponyms (on the material of the linguocultural dictionary) - Rysbergen Kyzdarkhan; Uali Nurgeldy; Fazylzhanova Anar; Kuderinova Kuralay (Open Linguistics)
The processes of objectification of rational and irrational types of knowledge in the cultural semantics of toponyms as a product of the mental activity of the subject (individual and ethnolinguistic collective) are considered. The analysis is carried out on the material of toponyms that involve colour values, numerals and phytonyms, mythonyms, etc. The rational type of knowledge contains rich empirical information with diverse cultural semantics. The irrational type of knowledge represents mythological, esoteric, animistic, religious ideas, superstitions, customs, and various folk beliefs with profound ethnosemantics. In rational knowledge, various aspects of the economic and practical life of nomads in the development of the surrounding reality are detailed. The irrational type of knowledge concentrates on value orientations, stereotypes and prejudices, and moral and ethical norms of the nomadic Kazakh ethnic community in the past, represented in the cultural semantics of the language matrix of folk geographical names. For the first time, the ethnoecological, ethnobotanical knowledge of the Kazakh people is presented in the language matrix of toponyms, in which the emphasis is shifted not to lexical features, but to the cultural aspect, to cultural semantics.